P2X7 receptor as an independent prognostic indicator in gastric cancer - Calik, Ilknur; Calik, Muhammet; Sarikaya, Burcu; Ozercan, Ibrahim Hanifi; Arslan, Ramazan; Artas, Gokhan; Dagli, Adile Ferda (Assoc Basic Medical Sci Federation Bosnia & Herzegovina Sarajevo, 2020)
Gastric cancer (GC) is one of the foremost causes of cancer-related death around the world. The P(2)X(7 )receptor (P2X7R), a member of the P2X7R subfamily of P(2 )receptors, is a unique molecule that has been shown to affect tumor growth and progression as well as various inflammatory processes, including proliferation of T lymphocytes, release of cytolcines. and production of free oxygen radicals. P2X7R has been established as a prognostic parameter in some cancers, and recently, it has been investigated in the development of new targeted therapies. In the present study. we aimed to investigate the prognostic value of P2X7R expression in GC. The expression profile of P2X7R was evaluated immunohistochemically in 156 paraffin-embedded human GC specimens. P2X7R expression was higher in patients with lymph node metastasis than in those without (p < 0.001). P2X7R overexpression was closely related with tumor-infiltrating lymphocytes (TILs) (p = 0.001), vascular invasion 0.006), depth of invasion (p < 0.001), distant metastasis (p < 0.001), and advanced tumor, node, metastasis stage (p < 0.001). Moreover, univariate (hazard ratio [HR] 3.98; 9596 confidence interval (Cl) 1.89-11.82;p < 0.001) and multivariate (HR 2.24; 9596 Cl 3.53-12.50;p < 0.001) Cox regression analysis showed that upregulated P2X7R expression clearly correlated with worsened overall survival. In summary, our data revealed that P2X7R may serve as a reliable prognostic parameter and promising therapeutic target for GC.
Keywords: Gastric cancer; P2X7 receptor; survival; tumor-infiltrating lymphocytes; prognosis